Performance characteristics of bioassay, UV-spectrophotometry and high performance liquid chromatographic determination of sparfloxacin in tablets - Marona, H. R N [UNESP]; Schapoval, E. E S [UNESP] (My University, 2001)
The microbiological bioassay, the UV-spectrophotometry and the high performance liquid chromatography (HPLC) methods for assaying sparfloxacin in tablets were compared. The accuracy, repeatability, and precision of each method was assessed and precise. All methods were reliable within acceptable limits for antibiotic pharmaceutical preparations being accurate and precise. The microbiological bioassay and HPLC are more specific than UV-spectrophotometric analysis. However, the microbiological bioassay requires 20 h to get results, and HPLC is the most expensive analysis. The application of each method as a routine analysis should be investigated considering cost, simplicity, equipment, solvents, speed, and application to large or small workloads.
Keywords: Bioassay; Fluoroquinolone; HPLC; Pharmaceutical analysis; Sparfloxacin; UV-spectrophotometry; antibiotic agent; quinoline derived antiinfective agent; sparfloxacin; analytic method; bioassay; cost; drug determination; drug structure; high performance liquid chromatography; liquid chromatography; nonhuman; spectrophotometry; tablet formulation; ultraviolet spectrophotometry